Investigating Intraoperative and Intraprofessional Handoffs in Anesthesia. (September 2018) - Jurewicz, Katherina; Alfred, Myrtede; Neyens, David M.; Catchpole, Ken; Joseph, Anjali; Reeves, Scott T.
Handoffs occur frequently in healthcare systems, and miscommunications and critical omissions within handoffs have been linked to serious medical errors. Handoff quality is a priority of patient safety initiatives across several international organizations. The majority of previous research in handoffs have focused on postoperative handoffs; yet, there is a need to specifically investigate intraoperative handoffs, especially within individual professions or subspecialties. Each subspecialty within a surgical team may approach handoffs differently. The anesthesia team is especially unique as they take a team-based approach to patient care where multiple anesthesia providers may be involved in one surgical case. We describe an observational study of intraoperative and intraprofessional handoffs in anesthesia. Temporary and permanent handoffs were investigated as well as the contextual elements that influenced handoff procedures. In a sample of 35 video recorded surgeries, a total of 16 handoffs were identified for the maintenance phase of surgery. These handoffs ranged between 33 seconds and 7.42 minutes in duration. Our study revealed variability in intraoperative handoffs during the maintenance phase of anesthesia and emphasizes that intraoperative and intraprofessional handoffs warrant more in-depth examination in order to develop effective strategies or tools for high quality handoffs in anesthesia.